A new species of the Cyrtodactylus irregularis complex (Squamata: Gekkonidae) from southern Vietnam - Geissler, Peter; Nazarov, Roman; Orlov, Nikolai L.; Böhme, Wolfgang; Phung, Trung My; Nguyen, Truong Quang; Ziegler, Thomas (Zootaxa, 2009)
We describe a new species of the genus Cyrtodactylus from southern Vietnam, based on voucher specimens collected from Dong Nai and Ba Ria – Vung Tau provinces. Cyrtodactylus cattienensis sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: size small, with a maximum SVL of 69 mm; neck band present, extending to the posterior margin of the eye; trunk, tail and limbs bearing irregularly shaped bands: 4–6 light bands on trunk and 4–12 white bands on tail; 16–22 irregular longitudinal rows of dorsal tubercles; 28–42 longitudinal rows of ventrals at midbody; lateral folds weakly developed or absent, without enlarged tubercles; tail not depressed, not enlarged at base, scales arranged in whorls; males with 6–8 precloacal pores in angular continuous series; a patch of enlarged precloacal scales present in both sexes; 3–8 slightly enlarged femoral scales on each hind limb in both sexes; femoral pores absent; precloacal groove absent; subcaudal scales small, not transversely enlarged.